The Impassibility of God and the Problem of Evil - Surin, Kenneth (Scottish journal of theology, 1982)
According to a certain strand in the orthodox Christian theist tradition, God's impassibility is engendered by his immutable nature. For if God cannot change then he cannot experience pain or sorrow. This fundamental principle was appropriated from Plato, who maintained that a being who is perfect can experience neither sadness, pain, nor sorrow. Some modern Christian theists, however, concede that this is perhaps the most questionable aspect of certain forms of orthodox Christian theism.